La Ville-de-Montereau - Muriel Berthou Crestey (Flaubert: Revue Critique et Génétique)
The Éducation sentimentale begins with a scene of people boarding a paddle-steamer, as Frédéric Moreau is going to meet his mother at Nogent-sur-Seine. La Ville-de-Montereau is the first proper noun of the incipit. This designation, long thought to have been invented by the author, is the name for a small boat that was indeed operating in 1840, as proven by a picture recently incorporated in Flaubertian studies. In what way can this image enrich our understanding of this strategic location? The iconographic study will be compared with the historical context and the textual genetic analysis.